Multiwalled Carbon Nanotube Photonic Crystals for Extreme-UV Photonics based on Comprehensive Dielectric Function Modeling - Yasser Shamssollahi; Mohammad Kazem Moravvej-Farshi (AUT Journal of Electrical Engineering, 2024)
Our latest study builds upon our previous research on multi-wall carbon nanotubes (MWCNTs) by exploring the photonic responses of regularly β-aligned arrays of these nanotubes. Through extensive calculations using the Finite Difference Time Domain Method, we determined that MWCNT-based photonic crystals possess significant Bragg reflections of up to 80% without experiencing substantial attenuation, even at wavelengths as low as 17 nm. This discovery is of great significance, as traditional materials have not been able to scatter UV photons within this frequency range efficiently. Following extensive research, we analyzed various model parameters such as lattice periodicity, inner and outer radii of MWCNTs, and the polarization (TM or TE) and direction (Γ-X or Γ-M) of the incident wave. Our findings present promising implications for advancing ultra-high-frequency photon manipulation in EUV applications, with potential developments ranging from UV laser mirrors to EUV lithography lenses, and beyond to UV spectroscopy collimators.